2020
DOI: 10.1016/j.carbpol.2019.115514
|View full text |Cite
|
Sign up to set email alerts
|

Alginate hydrogels for bone tissue engineering, from injectables to bioprinting: A review

Abstract: This review focuses on recently developed alginate injectable hydrogels and alginate composites for applications in bone tissue regeneration, and it evaluates the alternatives to overcome the problems that avoid their utilization in the field. Section 2 covers the properties of alginates that have made them useful for medical applications, in particular their ionic gelling ability for preparing injectable compositions used as delivery drugs systems. The advantages and shortcomings of these preparations are rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
248
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 406 publications
(250 citation statements)
references
References 203 publications
2
248
0
Order By: Relevance
“…The rigid, still injectable, hydrogel showed excellent mechanical properties and a nanofibrous architecture similar to the natural fibrillar bone one, guaranteeing excellent in vitro results in terms of cell viability, osteogenic differentiation and cell adhesion to the hydrogel fibres, using MC3T3-E1 cells [100]. Moreover, the alginate hydrogels has been involved as bioink for bioprinting in bone tissue regeneration field [101]. The excellent alginate properties were confirmed by a comparative study of hydrogels in bone tissue engineering that reported the alginate superiority in comparison to hyaluronic acid in bone tissue engineering, reveled by cell viability, proliferation, calcium content, osteocalcin level and osteogenic differentiation [102].…”
Section: Natural Polymersmentioning
confidence: 93%
“…The rigid, still injectable, hydrogel showed excellent mechanical properties and a nanofibrous architecture similar to the natural fibrillar bone one, guaranteeing excellent in vitro results in terms of cell viability, osteogenic differentiation and cell adhesion to the hydrogel fibres, using MC3T3-E1 cells [100]. Moreover, the alginate hydrogels has been involved as bioink for bioprinting in bone tissue regeneration field [101]. The excellent alginate properties were confirmed by a comparative study of hydrogels in bone tissue engineering that reported the alginate superiority in comparison to hyaluronic acid in bone tissue engineering, reveled by cell viability, proliferation, calcium content, osteocalcin level and osteogenic differentiation [102].…”
Section: Natural Polymersmentioning
confidence: 93%
“…Even though alginate has been declared safe for application in humans by the U.S. Food and Drug Administration (FDA) (de Vos et al, 2014;Xu and Lam, 2018), no devices for BTE have been commercialized so far. Interestingly, the use of alginates as bioinks for bioprinting is thought to be a valid opportunity for these hydrogels to expand their application in BTE (Hernández-González et al, 2020).…”
Section: Current Usementioning
confidence: 99%
“…CS has also been frequently combined with other polysaccharides, generally anionic, such as ALG or gellan gum (Table 6). Alginate forms readily stable hydrogels in the presence of divalent ions due to the interactions with carboxylic acid groups present on the polymeric chains and the formation of ionic bridges [253,254]. As tear secretion contains divalent ions, notably Ca 2+ ions, ALG, as well as gellan gum and other similar anionic polysaccharides, are good candidates for the preparation of ionically triggered in situ hydrogels.…”
Section: Other Polysaccharidesmentioning
confidence: 99%